Interpreting Accent Marks as Hiatus Indicators: Syllabification Intuitions for io Sequences in US Spanish - Beaton, Mary Elizabeth (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This study considers the syllabification perceptions of heritage speakers of Spanish (HSS), second language learners, and monolingual speakers in words with io sequences in order to understand the differences between HSS and the other two groups. Participants completed a reading task and then a listening task in which they indicated the number of syllables in each stimulus perceived. Three different lexical stress patterns were tested: stress on i (like río), stress on o (like pidió), and atonic syllables (like folio). The results show that heritage participants behave like monolinguals with audio stimuli, but in the reading task they interpret orthographic accent marks as indicators that two vowels should be divided into separate syllables. This leads to accurate interpretations of stimuli with stress on i, since Spanish phonology dictates that stressed high vowels are syllabified in hiatus. Atonic syllables, which lack an orthographic accent, are correctly syllabified as diphthongs. However, heritage participants were less accurate with stress on o because they treated these stimuli like those with stress on i. These findings have implications for both linguistic theory and for pedagogy